STRUCTURAL CHANGES IN THE PROCESS OF ORGANIZATIONAL TRANSFORMATIONS AT AN ENTERPRISE - MAZORENKO, Oksana; IVANCHENKOV, Viacheslav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article explores the critical role of structural changes in the process of organizational transformations within enterprises, focusing on how these changes impact organizational effectiveness and long-term development. In the current competitive and rapidly evolving business environment, enterprises are compelled to undergo continuous transformation to maintain their relevance and achieve strategic objectives. Structural transformations, which involve the reconfiguration of organizational hierarchies, roles, and workflows, are central to this process. The study examines various forms of structural changes, with a particular emphasis on the shared services model, which has emerged as a prominent approach for optimizing resource utilization and improving service delivery within enterprises. The shared services model involves the centralization of common functions—such as human resources, finance, and IT—into a single, unified service center that serves multiple business units within the organization. This approach not only leads to significant cost savings and process efficiencies but also facilitates standardization and consistency in service quality across the enterprise. By reducing duplication of efforts and streamlining operations, shared services enable organizations to better focus on their core competencies, thereby improving overall performance and competitiveness. The findings of this study underscore the importance of structural transformations as a strategic tool for enhancing organizational effectiveness. The article concludes that while structural transformations are often challenging, they are essential for organizations seeking to navigate the complexities of modern business environments and achieve sustainable growth.